Dietary Nannochloropsis oculata ameliorates lead acetate induced reproductive toxicity in Barki rams: NF-κB and cytokines pathways - Doaa H. Elsayed; Sameer A. Nagadi; Heba M.A. Abdelrazek; Ahmed. S. El‑Hawy; Moharram F. El-Bassiony; Seham A. Helmy; Yasmina K. Mahmoud; Ibrahim E. Helal; Shady T. Hassan (Ecotoxicology and Environmental Safety)
The study aimed to explore the protective effect of Nannochloropsis oculata (N.oculata) on lead induced reproductive toxicity in rams. Sixteen Barki rams were divided equally in to 4 groups; group A: control, group B: was administered 3 % dietary N. oculate, group C: was gavaged 5 mg/kg/day lead acetate and group D: was supplemented with 3 % dietary N. oculata and gavaged with 5 mg/kg/day lead acetate. The experiment lasted 180 days. Semen and blood samples were obtained. Ejaculates were examined for semen criteria besides, analysis of testosterone. Testicular oxidant/antioxidant markers, cytokines, gene expression of interleukin-6 (IL-6) and nuclear factor Kappa B (NF-κB) were estimated. Alga-treated rams revealed significant upgrades in semen criteria, serum testosterone and reduced glutathione (GSH); meanwhile, downregulation in malondialdehyde (MDA), IL-4, IL-2 as well as gene expressions of IL-6 and NF-κB as compared to other treated groups. However, lead-treated rams showed significant deteriorations in semen criteria and reduced GSH while significant elevations in MDA, IL-4, IL-2 as well as gene expression of IL-6 and NF-κB were noticed than control. Alga supplementation to lead-intoxicated rams significantly upgraded the lead induced alterations that were manifested by improvement in testicular histopathology. In conclusion, the addition of alga mitigated lead induced reproductive toxicity in rams via improving testosterone, oxidant/antioxidant status, semen criteria and reducing inflammatory cytokines.